Digital Marketing Strategies to Increase Customer Purchase Decisions in the Frozen Food Industry: A Case Study of the Sunny Gold Brand - Olivia Henson; Ari Mulianta Ginting (Dinasti Review, 2025)
The digital transformation in the modern business landscape has compelled companies to optimize their marketing strategies in order to influence customer purchase decisions more effectively. However, increased investments in digital marketing have not always been accompanied by proportional sales growth, as exemplified by SunnyGold. This inefficiency highlights the urgent need to identify digital marketing strategies that can effectively drive consumer purchasing behavior but also maximize marketing expenditure. This study aims to examine the influence of digital marketing strategies including Advertising, Social Media Marketing, and Search Engine Marketing (SEM) on Customer Purchase Decisions, with Brand Image serving as a mediating variable, in the context of Indonesia’s frozen food industry, using SunnyGold as a case study. Employing a quantitative research approach, the study gathered data from 343 respondents who are consumers of SunnyGold nugget products. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.1.2 software. The findings reveal that Advertising, Social Media Marketing, and SEM have a positive and significant impact on Customer Purchase Decisions. Moreover, Brand Image is proven to mediate the effects of Advertising and Social Media Marketing on Customer Purchase Decisions. These results underscore the importance of integrating various digital marketing elements to design effective strategies that enhance customer purchase behavior. The study contributes to digital marketing literature and provides practical recommendations for frozen food industry practitioners in crafting more targeted and efficient marketing strategies in the digital era.